Pharmacobotanic characterization of young stems and stem barks of Rauvolfia sellowii Müll. Arg., Apocynaceae - Leopoldo Clemente Baratto; Márcia do Rocio Duarte; Cid Aimbiré de Moraes Santos (Universidade de São Paulo, 2010)
Rauvolfia sellowii Müll. Arg. (Apocynaceae), a Brazilian native tree rich in indole alkaloids, is known as "pau-pra-tudo" and popularly used as hypocholesterolemic, hypoglycemic and antihypertensive. The aim of this work was to study the anatomy of the young stems and stem barks of this medicinal plant, in order to contribute to the identification of the species as a drug. The plant material was fixed and prepared according to standard microtechniques. The young stems have remaining epidermis, but a suberified peridermis is evident. The phellogen is located in the cortical region, forming suber externally. Underneath the phellogen, lies the phelloderm and collenchymatic region. In the cortex, there are numerous laticifers and some fibers. There is an incomplete sclerenchymatic sheath, consisting of several groups of fibers and stone cells. The stem has internal phloem ordered as isolated groups side by side. Numerous laticifers, calcium oxalate crystals, idioblasts and amyloplasts are found in the cortex, phloem, xylem and pith. The stem bark has many layers of suber and cortical parenchyma, a sheath composed of fibers and stone cells totally lignified, and external phloem. These anatomical characteristic, taken together, can be used as quality control parameters for this species. Rauvolfia sellowii Müll. Arg. (Apocynaceae), uma árvore nativa brasileira rica em alcaloides indólicos, é conhecida como "pau-pra-tudo" e utilizada popularmente como hipocolesterolêmica, hipoglicêmica e anti-hipertensiva. O presente trabalho teve como objetivo caracterizar anatomicamente o caule jovem e a casca caulinar dessa planta medicinal, a fim de contribuir para a identificação e autenticidade da droga. O material vegetal foi fixado e submetido às microtécnicas usuais. O caule jovem possui epiderme remanescente, porém uma periderme suberificada é observada. O felogênio instala-se na região cortical, formando súber externamente. Subjacentes ao felogênio são observadas a feloderme e uma região colenquimática. No córtex, há numerosos laticíferos e algumas fibras. Há uma bainha esclerenquimática incompleta, constituída de vários grupos de fibras e células pétreas. O caule mostra floema interno organizado em grupos isolados lado a lado. Numerosos laticíferos, cristais de oxalato de cálcio, idioblastos e amiloplastos são encontrados no córtex, no floema, no xilema e na medula. A casca do caule possui várias camadas de súber e parênquima cortical, uma bainha composta de fibras e células pétreas totalmente lignificadas, e floema externo. Estes caracteres anatômicos, quando analisados em conjunto, podem ser utilizados como parâmetros para controle de qualidade desta espécie.